The Directly Observed Therapy Short-Course (DOTS) strategy in Samara Oblast, Russian Federation - Balabanova,Y; Drobniewski,F; Fedorin,I; Zakharova,S; Nikolayevskyy,V; Atun,R; Coker,R (Respiratory Research, 2006)
Background: The World Health Organisation (WHO) defines Russia as one of the 22 highest-burden countriesfor tuberculosis (TB). The WHO Directly Observed Treatment Short Course (DOTS) strategy employing astandardised treatment for 6 months produces the highest cure rates for drug sensitive TB. The Russian TBservice traditionally employed individualised treatment.The purpose of this study was to implement a DOTS programme in the civilian and prison sectors of SamaraRegion of Russia, describe the clinical features and outcomes of recruited patients, determine the proportion ofindividuals in the cohorts who were infected with drug resistant TB, the degree to which resistance was attributedto the Beijing TB strain family and establish risk factors for drug resistance.Methods: prospective studyResults: 2,099 patients were recruited overall. Treatment outcomes were analysed for patients recruited up tothe third quarter of 2003 (n = 920). 75.3% of patients were successfully treated. Unsuccessful outcomes occurredin 7.3% of cases; 3.6% of patients died during treatment, with a significantly higher proportion of smear-positivecases dying compared to smear-negative cases. 14.0% were lost and transferred out. A high proportion of newcases (948 sequential culture-proven TB cases) had tuberculosis that was resistant to first-line drugs; (24.9%isoniazid resistant; 20.3% rifampicin resistant; 17.3% multidrug resistant tuberculosis). Molecular epidemiologicalanalysis demonstrated that half of all isolated strains (50.7%; 375/740) belonged to the Beijing family. Drugresistance including MDR TB was strongly associated with infection with the Beijing strain (for MDR TB, 35.2%in Beijing strains versus 9.5% in non-Beijing strains, OR-5.2. Risk factors for multidrug resistant tuberculosis were:being a prisoner (OR 4.4), having a relapse of tuberculosis (OR 3.5), being infected with a Beijing family TB strain(OR 6.5) and having an unsuccessful outcome from treatment (OR 5.0).Conclusion: Th